Macroeconomic Determinants of Islamic Mutual Fund ROI in Indonesia: Faktor Penentu Makroekonomi ROI Reksa Dana Syariah di Indonesia - Ramadhini, Suci; Harahap, Muhammad Ikhsan; Daulay, Aqwa Naser (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Islamic mutual funds in Indonesia have grown rapidly as ethical investment instruments aligned with sharia principles. Specific Background: Their performance, however, remains sensitive to macroeconomic dynamics such as inflation, BI Rate, and economic growth (GDP). Knowledge Gap: Previous studies often use Net Asset Value (NAV) as a proxy for performance and show inconsistent results, while limited attention is given to ROI as a direct measure of investor returns. Aims: This study aims to analyze the effect of inflation, BI Rate, and GDP on the Return on Investment (ROI) of Islamic mutual funds in Indonesia from 2020 to 2024. Results: Using monthly secondary data and multiple linear regression, the findings show that inflation and the BI Rate have a significant positive effect on ROI, while GDP has a significant negative effect. Novelty: This study differs from previous research by using ROI instead of NAV and includes the latest post-pandemic data, providing more relevant empirical insights. Implications: These results suggest that Islamic mutual funds are more responsive to inflation and monetary policy than to general economic growth, offering valuable considerations for sharia fund managers and policymakers in formulating adaptive investment strategies.Highlight : Inflation and BI Rate positively influence Islamic mutual fund performance. Economic growth shows a negative effect on ROI of Islamic mutual funds. ROI is used as the main metric to assess investment success Keywords: Inflation, BI Rate, Economic Growth, Islamic Mutual Funds, Return on Investment Ask Chat